Die Nichtanwendung deutscher unionsrechtswidriger Gesetze: Verfassungsrechtliches Erfordernis eines umfassenden Verwerfungsmonopols des Bundesverfassungsgerichts - Karaosmanoglu, Cem (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
The book analyses the competence of courts to disregard national statutes that are in violation of European Union law. A problem that is not only highly relevant from the practical perspective but also increasingly pressing. Addressing legal history and jurisprudence to date, the research questions and examines the legitimacy and the limitations of the primacy of application of Union law as well as the principle of effectiveness. In that light, it is submitted that the Basic Law of the Federal Republic of Germany demands an encompassing exclusive power of the Federal Constitutional Court to reject national statutes contravening Union Law, and that this does not contradict European Union law. Lastly, the study suggests a feasible procedure that assimilates into existing and practiced multilevel cooperation of courts in the European Union: applying Article 100 Sec. 1 of the Basic Law analogously.